Analisis Kesan Program Peningkatan Kompetensi Guru dalam Mengembangkan Bahan Ajar Berbasis ICT dalam Menghadapi Pandemic - Iqbal Miftakhul Mujtahid; Susilawati Susilawati; Rian Vebrianto; Musa Thahir; Miftah Audhiha (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This activity aims to analyze the teacher's impression of the teacher competency improvement program in developing ICT-based teaching materials in dealing with the pandemic that has been implemented. This research is a Participatory Action Research (PAR) study with a qualitative descriptive approach. Participants who took part in the service program consisted of 25 teachers at SMA Negeri 1 Tembilahan. Data were obtained through questionnaires and descriptive analysis using SPSS version 26 for windows. The service program assessment consists of 3 constructs in which the results of the material constructs are obtained an average of 4.19 with good categories, the material delivery constructs are obtained an average of 4.36 with good categories and discussions/questions and answers obtained an average of 3.07 with good categories. So it can be concluded that the teacher competency improvement program in developing ICT-based teaching materials in dealing with the pandemic has a good impression on the participants.